Quality of palliative care. Perspective of Lebanese patients with cancer - Doumit, Myrna (2012)
The number of cancer patients in Lebanon is increasing, and patients are living longer due to early detection and enhanced methods of treatment. The purpose of this study was to evaluate the quality of life, symptom management, functional ability, and the quality of palliative care in adult Lebanese cancer patients at the American University of Beirut-Medical Center. A cross sectional survey design was used. A number of internationally validated instruments were translated into Arabic. A total of 200 cancer patients participated in the study; the majority was female with breast cancer and mean age 54. The cognitive functioning domain of the Quality of Life scale was found to have the highest score and social functioning the lowest. The most prevalent symptom was lack of energy and the least prevalent was shortness of breath. Nausea and pain were the symptoms mostly treated. In conclusion, this sample reported a fair quality of life and social functioning with high prevalence of physical and psychological symptoms. Inadequate symptom management was reported especially for the psychological symptoms. Participants reported a satisfactory level with the quality of care. Based on these results, providing adequate symptom management and social support to Lebanese cancer patients is highly recommended.